Kuliner sebagai Ekspresi Gaya Hidup: Studi Preferensi Restoran Modern di Kalangan Generasi Z dan Milenial - Septa Intiar; Dyan Tiana Putra (Pusat Riset dan Inovasi Nasional, 2025)
The development of the culinary industry in Indonesia shows significant changes, particularly among Generation Z and Millennials, who consume food not only for biological needs but also as a means of expressing their lifestyle and social identity. This study aims to explore the culinary preferences of young people toward modern restaurants in Semarang City and uncover the social and symbolic meanings behind their choices. A descriptive qualitative approach was employed using in-depth interviews, participatory observation, and digital documentation, involving 12 informants active on social media. The findings reveal that young people's culinary consumption is more oriented toward visual aesthetics, social recognition, and self-identity construction, closely aligned with lifestyle theory and social identity theory. Restaurant choices are influenced by atmosphere, interior design, and sustainability values, as well as the Instagram-worthy appeal of social media. These findings also confirm Pierre Bourdieu's concept of distinction, which states that culinary consumption serves as a symbol of status and the formation of social identity. This study offers insights for the culinary industry to design marketing strategies that align with the values and lifestyles of the younger generation.